APLIKASI EVWAN SEBAGAI EVALUASI KINERJA KARYAWAN PADA PT. MULTI STRUKTUR AROYA - Astuti, Reny Wahyuning (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2018)
Abstract â Decision support system (DSS) is part of a computer-based information system including a knowledge-based system or knowledge management is used to support decision making in an organization or company. Can also be regarded as a computer system that processes data into information for decision-making on specific semi-structured problems. As well as in PT. Multi Structure Aroya the absence of a ranking employee performance evaluation, the slow manufacture of employee performance evaluation reports. With the above problems it will build a decision support system with the calculation method Profile Matching by assuming that there is an ideal level of predictor variables that must be met by the subjects studied, rather than a minimum level which must be met or passed. Which is expected to overcome the existing problems in the system currently running. Data input is processed namely employee data, the data positions, the data value position and value profile employee profile. While the needs of the process is the calculation method Profile Matching. With the decision support system of employee performance evaluation using the Profile Matching method is expected to help the employee performance evaluation process more objective. Keywords : Decision Support Systems, EVWAN, Profile Matching.